The electromagnetic energy with the truncation method for a five-dimensional rotating black hole in a uniform magnetic field - Kaya, R.; Yilmaz, S. (SPRINGER/PLENUM PUBLISHERS, 2018)
We consider a charged five-dimensional Myers-Perry black hole in a uniform magnetic (test) field. Using the Komar mass formula, we calculate the total energy of the electromagnetic field within the truncation three-sphere for a five-dimensional rotating black hole with two equal-rotation parameters and two equal-magnetic field strengths. We show that the total electromagnetic energy takes the minimum value when the five-dimensional rotating black hole acquires a non-zero net electric charge Q.
Keywords: Myers-Perry metric; Komar mass formula; Energy-momentum tensor; DIMENSIONS; MILLIMETER; Astronomy & Astrophysics; Physics